Implementation of Environmental Care Education from Early Age - Sarisawati Intishar; Fathia Zaitun Azzahro; Ismi Hidayati Aris; Syukrotus Syukrotus; Zakiyah Isnawati; Ahmad Fauzan Hidayatullah (SEJ (Science Education Journal), 2020)
Environmental sustainability is a sensitive issue lately due to increased global warming, erratic weather, disturbed ecosystems, the emergence of diseases, and so on. Garbage, the beginning of environmental damage in the air, water, and soil. All alternative pathways to protect the environment will be in vain if it is not balanced with an attitude of caring for the environment. The aim is to provide education and information about the importance of environmental sustainability to young children. The research method is a literature review of research journal articles related to the application of environmental education from an early age. In the research, it is known that in general the productive age that plays a role in environmental problems range from 15-64 years. The introduction and character education of caring for the environment is an effort to help children to always care about the environment and protect nature. The character of caring for the environment needs to be instilled from an early age in order to be able to love the environment. Good behavior starts from simple activities since I was a child, because at this time the brain can quickly absorb all the information obtained. When in previous studies environmental character education is integrated with each subject through competency standards, active learning, and school culture. This study focuses on environmental sustainability character education in early childhood.